Effect of epidural volume extension with colloid on dose requirement for intrathecal spinal block: a double blind prospective study - Shyam, Radhey; Chaudhary, Ajay Kumar; Singh, Prithvi K.; Jain, Gaurav; Singh, Dinesh; Chandra, Girish; Bhatia, Vinod K. (International Journal of Research in Medical Sciences, 2016)
Background: Epidural volume extension (EVE) is a modification of combined- spinal epidural anaesthesia (CSEA) in which fluid is injected in epidural space after the intrathecal block. Fluid in epidural space compress subarachnoid space and causes cephalic spread of intrathecal drug to increase block height. Purpose of study is to determine efficacy of EVE on dose requirement of intrathecal bupivacaine when colloid was used for EVE. Methods: Sixty patients of ASA physical status I or II, scheduled for elective caesarean sections were recruited and randomized into two groups (30 each group). Group 1: CSEA in which spinal block is followed by 10 ml Colloid (HES 6%) in epidural space; Group 2: CSEA but no fluid in epidural space. Onset of sensory block and hemodynamic variables were measured at 5 min. intervals up to 40 minutes then at 10 min. intervals till end of surgery. Ineffective block was top- up by epidural 0.5% bupivacaine in incremental doses. Results: Median effective dose of intrathecal bupivacaine was significantly lower, 4.0 mg (95% CI 4.40-5.60) in group 1 versus 7.0 mg (95% CI 6.93-7.61) in group 2. Only 11 patients required ephedrine in group 1 versus 20 in group 2. Requirement of ephedrine was significantly lower 2.20 (±2.94) mg in group 1 versus 4.0 (±2.88) mg groups 2. Changes in haemodynamic variables from baseline were significantly lower in group 1 than those in group 2. Conclusions: EVE with colloid was effective in lowering dose requirement of spinal bupivacaine while patients hemodynamically were more stable.